2014
DOI: 10.1038/npp.2014.331
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal vs Genetic Programming of Serotonin States Associated with Anxiety

Abstract: Large numbers of women undergo antidepressant treatment during pregnancy; however, long-term consequences for their offspring remain largely unknown. Rodents exposed to serotonin transporter (SERT)-inhibiting antidepressants during development show changes in adult emotion-like behavior. These changes have been equated with behavioral alterations arising from genetic reductions in SERT. Both models are highly relevant to humans yet they vary in their time frames of SERT disruption. We find that anxiety-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
61
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 85 publications
(134 reference statements)
3
61
0
Order By: Relevance
“…31,48 Increased synthesis could contribute to an increase in the readily releasable pool of serotonin; this pool is known to be sensitive to changes in uptake and synthesis. 49 Although the current study does not provide direct evidence for differences in serotonin release per se, we hypothesize that presynaptic serotonin 1A autoreceptor desensitization/downregulation, 47,50 in conjunction with increased synthesis, 48 Mice genetically lacking SERT were previously discovered to show a loss of frequency-dependent serotonin release when brain slices containing the substantia nigra were investigated by FSCV. 51 The authors concluded that abolishing SERT leads to a large summation of extracellular serotonin regardless of stimulus strength.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…31,48 Increased synthesis could contribute to an increase in the readily releasable pool of serotonin; this pool is known to be sensitive to changes in uptake and synthesis. 49 Although the current study does not provide direct evidence for differences in serotonin release per se, we hypothesize that presynaptic serotonin 1A autoreceptor desensitization/downregulation, 47,50 in conjunction with increased synthesis, 48 Mice genetically lacking SERT were previously discovered to show a loss of frequency-dependent serotonin release when brain slices containing the substantia nigra were investigated by FSCV. 51 The authors concluded that abolishing SERT leads to a large summation of extracellular serotonin regardless of stimulus strength.…”
Section: Resultsmentioning
confidence: 67%
“…Neuroadaptive desensitization of serotonin 1A autoreceptors in KO-M mice occurs. 47 This prevents autoinhibitory dampening of serotonin release and could lead to higher basal and stimulated dialysate serotonin levels in KO-M mice. By contrast, in WT-M-ESC mice, SERT inhibition is limited to striatal serotonergic terminals; somatodendritic SERT and serotonin 1A autoreceptors in the raphe presumably function normally.…”
Section: Resultsmentioning
confidence: 99%
“…7 These behaviors in rodents have strong correlations with aspects of human anxiety and depression. Genetic reductions in SERT drive neuroadaptive alterations in the serotonin system, including increased extracellular serotonin concentrations, 8 decreased serotonin 1A autoreceptor function, 9 and reduced intracellular (recycled) serotonin accompanied by compensatory increases in serotonin synthesis (Figure, C). Observations in rodent models support the notion of reduced serotonin availability, either through relative deficits in serotonin recycling (eg, via reduced SERT) or serotonin synthesis as critical mechanisms by which the buffering of emotional stress is affected in anxious and depressed states.…”
Section: +mentioning
confidence: 99%
“…Moreover, adaptive changes in the development of the serotonin system and its targets in brain circuitry underlying fear-and anxiety-related behavior occur in response to early life alterations in serotonin transmission associated with constitutive or environmental factors. 9 Current understanding of the neural systems basis for social anxiety disorder emphasizes abnormal, traitlike dysfunction in distributed circuits involving the amygdala, insula, hippocampus, and orbital frontal regions.…”
Section: +mentioning
confidence: 99%
“…Using a strain of mice genetically engineered to lack serotonin transporter (SERT) expression 2 and previously reported NSF test parameters, 3 we were initially unable to observe increased anxiety-related behavior commonly associated with constitutive loss of SERT, as determined in the NSF and other anxiety-related behavior tests (Figure 1A). 2, 45 As such, we embarked on a systemic investigation aimed at varying key NSF test parameters.…”
mentioning
confidence: 93%